2021
DOI: 10.3390/medicina57040394
|View full text |Cite
|
Sign up to set email alerts
|

Association between Lower Urinary Tract Symptoms and Sleep Quality of Patients with Depression

Abstract: Background and Objectives: In the general population, sleep disorders are associated with lower urinary tract symptoms (LUTS) including urinary incontinence (UI). This connection has not been explored fully in specific patient groups. Thus, we investigated the association between sleep quality and LUTS for patients with depression. Materials and Methods: This study was prospective and cross-sectional. We analyzed questionnaire data on depression, sleep quality, LUTS, and UI from depressed patients treated in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…During the nighttime, they visited the bathroom a few times, and their sleep was affected significantly. Interrupted sleep led to problems in occupational functioning, as well as psychological functioning, as it worsened depression [ 7 ]. Pregnant women may experience a multidimensional negative impact on QoL, such as social-emotional relationships, physical activities, employment issues, limitation to travel, sleep disruption, and obstacles in performing their prayers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the nighttime, they visited the bathroom a few times, and their sleep was affected significantly. Interrupted sleep led to problems in occupational functioning, as well as psychological functioning, as it worsened depression [ 7 ]. Pregnant women may experience a multidimensional negative impact on QoL, such as social-emotional relationships, physical activities, employment issues, limitation to travel, sleep disruption, and obstacles in performing their prayers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nocturia has been shown to have close relationships with early waking and decreased total sleep time 23 . In a cohort of patients treated for depression, depression severity significantly correlated with sleep quality 24 . Przydacz et al 25 even argued that it was not depression severity, but rather sleep quality that correlated with nocturia.…”
Section: Discussionmentioning
confidence: 97%
“…However, frequent night urination is significantly associated with reduced time and quality of sleep, thus, leading to chronic day‐time tiredness and circadian rhythm disruption 76 . Reduced sleep quality and time can also cause hormonal abnormalities, including low testosterone, increased stress hormone levels such as cortisol, and lower thyroid levels which in turn could be associated with increased circadian rhythm disruption 77,78 . Furthermore, Arauju et al found that poor sleep quality increased the risk of obstructive and irritative LUTS, and sleep restriction increased the risk of irritative LUTS by twofold.…”
Section: Discussionmentioning
confidence: 99%
“…76 Reduced sleep quality and time can also cause hormonal abnormalities, including low testosterone, increased stress hormone levels such as cortisol, and lower thyroid levels which in turn could be associated with increased circadian rhythm disruption. 77,78 Furthermore, Arauju et al found that poor sleep quality increased the risk of obstructive and irritative LUTS, and sleep restriction increased the risk of irritative LUTS by twofold. This study however did not evaluate specifically a diagnosis of BPH, but rather only general LUTS.…”
Section: A Potential Association Between Development and Progression Ofmentioning
confidence: 99%